DESIGNING LIFE SKILL – BASED ENGLISH READING MATERIALS FOR SECOND GRADE STUDENTS OF SMA NEGERI 1 PRINGGASELA - saputra, ari; sutarman, sutarman; Syamsurrijal, Syamsurrijal (LPPM Universitas Bumigora Mataram, 2020)
This research aims to: developing life skill-based English reading materials design for the second grade students of SMA NEGERI 1 PRINGGASELA. The design used in this research is report design by using R&D ( Research and Development ) approach. The subjects of this research are the second grade students of SMA Negeri 1 Pringgasela in academic year 2016/2017. There are 35 students. In collecting data, the researcher uses two steps. First, the researcher distributed questionnaires into the students. Second, the researcher gathers data for conducting evaluation, opinion and suggestion from an English Teacher of SMAN 1 Pringgasela and an expert of designed materials. All responses and comments to the open questions were reviewed and grouped into some meaningful categories as they provide useful information for revising the product. To determine the readability level of the texts used in new developed reading materials, the following are the categories of readability level and reader grade level according to Flesch Readability East Formula and Flesch-Kincaid Grade Level. Scores between 90.0 and 100.0, considered easily understandable. Scores between 60.0 and 70.0, considered easily understood. Scores between 0.0 and 30.0, considered easily understood. The final product of the materials consists of a course material of Life Skill Based English Material and a teacher’s manual. Whole Language Reading provides rich input of reading strategies, variety of topics, concepts, texts, activities, tasks, and evaluations. Using this material makes reading more holistic and meaningful as it provides integration across language skills and subject areas. Educational institutions need to provide a rich learning environment with a variety of reading sources, print and digital to provide opportunities for students to choose and determine reading materials that suit their needs.